Cochlear implantation through the middle fossa: an anatomic study for a novel technique. (September 2013) - Brito, Rubens de; Bittencourt, Aline Gomes; Tsuji, Robinson Koji; Magnan, Jacques; Bento, Ricardo Ferreira
Abstract Conclusion: The technique proposed is simple, reliable, and provides sufficient exposure of the basal portion of the cochlea while avoiding disabling complications. It enables visualization of the cochlear basal turn and the osseous spiral lamina, facilitating the insertion of the cochlear implant array through the scala tympani. Objectives: To describe a novel approach for exposing the cochlear basal turn for cochlear implantation through the middle cranial fossa. Methods: Fifty temporal bones were dissected and a cochleostomy was performed via a middle fossa approach on the most superficial part of the cochlear basal turn, using the superior petrosal sinus, the skeletonized petrous apex, the lateral surface of the meatal plane trailed on the petrous apex from its most proximal portion, and the great superficial petrosal nerve as landmarks. The distance between the landmarks and the distance between the cochleostomy and the round window were measured. Results: In all temporal bones, only the top portion of the cochlear basal turn was uncovered. The cochleostomy allowed both the scala tympani and the vestibule to be exposed. A computed tomography scan of the temporal bones was performed to document the electrode insertion from the cochlear basal turn until its apex. The mean ± SD minor and major distances between the cochleostomy and the meatal plane were estimated to be 2.48 ± 0.88 mm and 3.11 ± 0.86 mm, respectively. The mean distance from the cochleostomy to the round window was 8.38 ± 1.96 mm, and that to the superior petrosal sinus was 9.19 ± 1.59 mm. The mean minor and major distances between the cochleostomy and the long axis of the meatal plane from its most proximal portion were estimated to be 6.63 ± 1.38 mm and 8.29 ± 1.43 mm, respectively.